IMPLEMENTATION OF SELF-ORDER IN IMPROVING SERVICE QUALITY AT KAFE PYUR 2.0 - Jufri, Alda Aprilia; Muhammad, Ashar (Politeknik STIA LAN Makassar, 2024)
Manual menu ordering has become a serious issue faced by Kafe Pyur 2.0. Customers must approach the cashier, select their menu, and make payment at the cashier's desk, resulting in long queues as only one cashier is available to serve them. This study aims to examine the impact of implementing self-ordering in improving service quality at Kafe Pyur 2.0. The research employs a quantitative method with a descriptive approach. It was conducted at Kafe Pyur 2.0, located on Jl. Sunu, Suangga, Makassar City, South Sulawesi. The study was carried out over approximately four months, from April 2024 to July 2024. The self-ordering system was developed using the existing POS Majoo application, which features a web order capability that allows business owners to create a self-ordering system for Kafe Pyur 2.0. Data collection was conducted through questionnaires. The results of the study revealed that the implementation of self-ordering at Kafe Pyur 2.0 can minimize queues, enabling customers to spend less waiting time when placing their orders. This has positively impacted the service quality, which was measured using the TERRA service quality dimensions comprising Tangible (physical evidence), Empathy, Reliability, Responsiveness, and Assurance. Based on these measurements, several issues were resolved, including enabling customers to order from anywhere within the scope of Kafe Pyur 2.0, thus preventing customer congestion and long queues, providing faster and more accurate menu availability information, and ensuring quicker order placement.